Soil organic carbon contents and their major influencing factors in mangrove tidal flats: a comparison between estuarine and non-estuarine areas - Ting Wu; Jia Guo; Gang Li; Yu Jin; Wei Zhao; Guangxuan Lin; Fang-Li Luo; Yaojun Zhu; Yifei Jia; Li Wen (Ecological Processes)
Abstract Background Unvegetated tidal flats of mangrove ecosystems in estuarine and non-estuarine areas play a crucial role in the coastal blue carbon sinks and biogeochemical cycle. However, there is still a lack of comprehensive understanding of the differences in soil organic carbon (SOC) contents in mangrove tidal flats between estuarine and non-estuarine areas, as well as their influencing factors. Methods In this study, soil samples were collected from estuarine and non-estuarine mangrove tidal flats in the Leizhou Peninsula. We compared the SOC and soil physicochemical properties between estuarine and non-estuarine mangrove tidal flats. The Random Forest algorithm was employed to identify the main influencing factors affecting SOC. The direct and indirect effects of the main influencing factors on SOC were studied using partial least squares structural equation modeling. Results SOC, total nitrogen (TN), total phosphorus (TP), available potassium (AK), clay, silt, aluminum (Al), lithium (Li), boron (B), molybdenum (Mo), and cadmium (Cd) contents in the estuarine areas were significantly higher than those in the non-estuarine areas of the mangrove tidal flats. The soil particle size (clay, silt, and sand), soil nutrient (TN and TP), and soil metal elements (Al, Mo, and Cd) were the main influencing factors of the SOC contents in the estuarine and non-estuarine mangrove tidal flat areas. Soil particle size (clay, silt, and sand) indirectly positively influenced SOC contents by positively influencing soil nutrient (TN and TP). Conclusions Our findings indicate that estuarine tidal flats have higher capacity of SOC sequestration compared with non-estuarine tidal flats. The main cause is that soil particle size has the potential to significantly increase SOC content by increasing soil nutrients, while metal elements have a direct influence on SOC content. The findings of the present study highlight an important mechanism that influences SOC contents in estuarine and non-estuarine mangrove tidal flats.